The Role of Video Games in Enhancing English Vocabulary Language Learning - Kurniawan, Ary; Rahmawati, Yeni (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the role of video games on English vocabulary language learning among first-year Mechanical Engineering students at Universitas Muhammadiyah Kalimantan Timur (UMKT). A descriptive quantitative design was applied. The studys population was comprised of 135 first-year Mechanical Engineering students. The researcher used a simple random sampling technique and the Slovin formula with a 5% margin of error. Data collection was conducted using a validated questionnaire adapted from previous researchers. The questionnaire included a close-ended to measure engagement, motivation, and experiences with video games for vocabulary learning. The results indicate that students who engage in video gaming, especially multiplayer games, improve speaking, reading, and vocabulary acquisition.